Peran Transformasi Digital dalam Meningkatkan Efisiensi Kerja, Kualitas Akuntansi, dan Audit Internal: Systematic Literature Review - Jawziyah Khaerullah; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the role of digital transformation in enhancing work efficiency, accounting quality, and internal audit effectiveness through a Systematic Literature Review (SLR) approach. The study adopts a non-empirical design by synthesizing conceptual and empirical findings from reputable international databases, following the PRISMA protocol to ensure transparency and methodological rigor. The results indicate that digital transformation, driven by technologies such as artificial intelligence, big data analytics, cloud computing, and blockchain, significantly improves operational efficiency while strengthening accounting quality through greater accuracy, transparency, and timeliness of financial reporting, alongside the evolution of internal audit into a more strategic and data-driven function. The findings also reveal an interconnected relationship among these dimensions, contributing to overall organizational performance and supporting sustainable outcomes in the digital era.